2018
DOI: 10.1186/s12870-018-1483-2
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of small RNAs revealed the diversified cold-responsive pathways during cold stress in the wild banana (Musa itinerans)

Abstract: BackgroundCold stress is one of the most severe abiotic stresses affecting the banana production. Although some miRNAs have been identified, little is known about the role of miRNAs in response to cold stress in banana, and up to date, there is no report about the role of miRNAs in the response to cold stress in the plants of the cultivated or wild bananas.ResultHere, a cold-resistant line wild banana (Musa itinerans) from China was used to profile the cold-responsive miRNAs by RNA-seq during cold stress. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 176 publications
(184 reference statements)
1
27
0
Order By: Relevance
“…The experimental strategy applied in this study was designed to investigate the profile of grapevine miRNAs in response to fungal infection in vitro because there are no unpredictable abiotic factors. Plant-pathogen interactions were entirely dissociated from the environment, which is usually used in the sRNAs profiling of stressed plants [57,58]. Ma et al [58] also found that the fungal sRNA enrichment was lower in planta than during in vitro growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental strategy applied in this study was designed to investigate the profile of grapevine miRNAs in response to fungal infection in vitro because there are no unpredictable abiotic factors. Plant-pathogen interactions were entirely dissociated from the environment, which is usually used in the sRNAs profiling of stressed plants [57,58]. Ma et al [58] also found that the fungal sRNA enrichment was lower in planta than during in vitro growth.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-pathogen interactions were entirely dissociated from the environment, which is usually used in the sRNAs profiling of stressed plants [57,58]. Ma et al [58] also found that the fungal sRNA enrichment was lower in planta than during in vitro growth. In this study, we used the cultivar Chardonnay since it is a popular grapevine cultivar all around the world [59], and in previous research, it showed a high level of tolerance against natural infections of GTD pathogens in Italy [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxidase genes have been extensively studied in plants for their ROS-scavenging activity under various biotic and abiotic stresses, including chilling [73,74,75]. Similarly, Liu et al [76] recently investigated the prominent biological pathways engaged in wild banana tolerance to chilling. They observed significant changes in the sesquiterpenoid and triterpenoid biosynthesis, particularly cytochrome P450 genes, a finding that supports well the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…China is rich of wild banana species (Li et al 2017), many of which showed high resistance to both abiotic and biotic stresses, such as cold and banana wilt disease (Li et al 2015). In our previous study, we identified that Sanming wild banana showed the highest cold resistance (Liu, Cheng, Chen, et al 2018;), suggesting that it has great potential to be used in banana cold resistance breeding. Based on its phenotype characteristics, it was categorized into Musa itinerans, which is native to Southeast Asia and subtropical China (H€ akkinen et al 2008).…”
mentioning
confidence: 99%
“… 2018 ; Liu, Cheng, Lin, et al. 2018 ), suggesting that it has great potential to be used in banana cold resistance breeding. Based on its phenotype characteristics, it was categorized into Musa itinerans , which is native to Southeast Asia and subtropical China (Häkkinen et al.…”
mentioning
confidence: 99%